Phantom Tooth pain, is it Often a Trigeminal Neuralgia? - Yadav, Rekha (Eastern Green Neurosurgery, 2022)
Toothache, buccal pain, facial pains are common presentations in dental clinics. Among them, phantom tooth pain always hits as a trigeminal neuralgia. Though classical picture of trigeminal neuralgia usually does not present with solo toothache, which may sometime masks the whole scenario.